English For Chemistry Book As A Learning Resource In University - Siska Oktapianti (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2022)
This study is a specified inspection of the development of the chemistry educational sources. The purposes of this study are: (1) to develop a book “English for Chemistry”, (2) to assess the quality of the book based on appraisement of lecturers and students. The type of the research is R & D. There many stages carried out in this investigation developed by Borg & Gall. The instrument used to assess the quality of this book is a set of quality having some aspects and criteria. The evaluations included 6 aspects with 33 criteria for lecturers and 4 aspects with 25 criteria for students. The evaluation result is in qualitative data and then the result is analyzed by the ideal evaluation criteria category guide to determine the quality of the book. Based on lecturers’ assessments, the book has a good quality, going to the score of 116 out of 165 and ideal percentage 70.3%. Meanwhile, in students’ side, the book is also classified as a good quality, whose score is 103 out of 125 and ideal percentage 82.4%. Development english for chemistry book, helping student understand scientific words of chemistry in english.